2002
DOI: 10.1152/ajpgi.00235.2001
|View full text |Cite
|
Sign up to set email alerts
|

Gut-associated lymphoid T cell suppression enhances bacterial translocation in alcohol and burn injury

Abstract: The mechanism of alcohol-mediated increased infection in burn patients remains unknown. With the use of a rat model of acute alcohol and burn injury, the present study ascertained whether acute alcohol exposure before thermal injury enhances gut bacterial translocation. On day 2 postinjury, we found a severalfold increase in gut bacterial translocation in rats receiving both alcohol and burn injury compared with the animals receiving either injury alone. Whereas there were no demonstrable changes in intestinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
140
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(152 citation statements)
references
References 51 publications
12
140
0
Order By: Relevance
“…Additionally, the finding of Kavanaugh et al (2005) showed that the combined insult significantly increases bacterial growth in the small intestine on day two after injury. The ethanol alone group exhibited an increase in intestinal permeability on day one and not on day two (Choudhry et al, 2002;Kavanaugh et al, 2005;Li et al, 2006). No change in other parameters was noted in the ethanol alone group.…”
Section: Combined Effect Of Alcohol and Burn Injury On Intestinal Bacmentioning
confidence: 78%
See 3 more Smart Citations
“…Additionally, the finding of Kavanaugh et al (2005) showed that the combined insult significantly increases bacterial growth in the small intestine on day two after injury. The ethanol alone group exhibited an increase in intestinal permeability on day one and not on day two (Choudhry et al, 2002;Kavanaugh et al, 2005;Li et al, 2006). No change in other parameters was noted in the ethanol alone group.…”
Section: Combined Effect Of Alcohol and Burn Injury On Intestinal Bacmentioning
confidence: 78%
“…However, on day two, the burn alone group exhibited a tendency of an increase in bacterial growth (though not significant), intestinal permeability and number of bacteria in the mesenteric lymph nodes, and a decrease in intestinal T cell functions. Nonetheless, the changes in these above parameters were more severe in the group of rats that has undergone a combined insult of alcohol and burn injury (Choudhry et al, 2002;Kavanaugh et al, 2005). These results suggest that acute alcohol intoxication potentiated the effect of burn injury on all of the parameters listed above including intestinal bacterial growth and permeability.…”
Section: Combined Effect Of Alcohol and Burn Injury On Intestinal Bacmentioning
confidence: 79%
See 2 more Smart Citations
“…Numerous studies have demonstrated the detrimental effect of ethanol on immune function including decreased lymphocyte activation following antigen-stimulation, decreased neutrophil infiltration and phagocytic capability, and altered cytokine production by both T cells and macrophages [86][87][88][89][90][91]. The immunosuppression caused by ethanol is exaggerated when in association with burn injury and can result in increased susceptibility to bacterial infection [92][93][94][95]. Consistent with immune suppression in males following burn plus alcohol, flutamide had no effect on immune responses in sham animals but restored cellular proliferation and the DTH response in burned male mice [33].…”
Section: Burn and Co-morbidity Factorsmentioning
confidence: 99%